The success strategy of the mayor of Yogyakarta, Herry Zudianto (2001-2011) in carrying out bureaucratic reforms to create good governance - Abdul Fikri Wisudawan Siregar (Inspirasi & Strategi (INSPIRAT): Jurnal Kebijakan Publik & Bisnis, 2023)
The results of the study show that the successful strategy for bureaucratic reform of the Yogyakarta City Government is inseparable from the role and commitment of leaders in realizing bureaucratic reform. Yogyakarta Mayor Herry Zudianto for the 2001-2011 period has realized his commitment. This commitment can be seen from the transformative leadership pattern, while the transformational leadership pattern can be seen from the 4 transformational leadership characteristics, namely the four i's (idealized influence, inspirational motivation, intellectual stimulation and individual consideration). The next success strategy consists of 3 stages. First, the formulation of the strategy includes developing a vision and mission, setting long-term goals and determining the main strategy for implementing bureaucratic reform in the form of change management. Second, implementation of the strategy by making improvements in the area of ​​change in bureaucratic reform with reference to the bureaucratic reform road map from the Ministry of Administrative Reform and Bureaucratic Reform and the establishment of bureaucratic reform through the Mayor of Yogyakarta Decree Number 602/KEP/2007 concerning Implementation of Bureaucratic Reform in the Context of Realizing Governance the good one. Third, strategic evaluation by implementing internal and external evaluation through self-assessment of the implementation of bureaucratic reform, this evaluation is carried out to find out the obstacles in carrying out bureaucratic reform and through this evaluation the implementation of future bureaucratic reform can be carried out properly.